COMPARATIVE STUDY OF PATHOGENICITY BETWEEN ASPERGILLUS FUMIGATUS AND PENICILLIUM CHRYSOGENUM IN MICE - Yassein, S. N. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was conducted to compare between two types of opportunistic fungi (Aspergillus fumigatus and Penicillium chrysogenum) in concerning their pathogenicity after intraperitoneal inoculation of mice. A total of twenty four male albino mice were used in this study which divided equally into 3 groups, The first and second groups were inoculated with 0.2ml of 1x 107spores/ml of A. fumigatus and P. chrysogenum intraperitonially respectively, while the third group was inoculated with normal saline which served as control group. All animals were monitored for 2 weeks after infection. The blood samples were collected by heart puncture after 18 days post infection to isolate of serum that used for biochemical analysis of liver and kidney functions. After that, all animals were sacrificed. Some internal organs of infected groups (liver, kidney, intestine, heart, spleen and lung) were taken to study the histopathological changes. It was found that there was severe histopathological changes in studied organs of infected mice particularly liver, kidney, spleen and intestine which corresponding with significant variation (p<0.01) in enzyme activities of liver and kidney like (Alanine Aminotransferase (ALT), Urea and Creatinine). Also, It was found that P. chrysogenum had more impact on these enzymes (15.65 ± 0.78, 135.23 ± 8.75 and 0.928 ± 0.02 respectively) than A. fumigatus (21.70 ± 1.04, 57.91 ± 5.99 and 0.587 ± 0.03 respectively). Therefore, the present study indicated that fungi present in the environment can induce severe inflammation reach to tissue damage in most vital internal organs So, further studies should be performed to determine the specific virulence factors and active components, which are responsible for pathogenesis of A. fumigatus and P. chrysogenum in spite of the fact that P. chrysogenum can produce antibiotic.